Analisis Kadar Nitrit pada Daun Katuk dan Daun Pegagan dengan Pereaksi Griess: Analysis of Nitrite Levels in Katuk Leaves and Pegagan Leaves with Griess Reagent - Emma Emawati; Egy Rizky Maulana; Fauzan Zein Muttaqin; Lilis Silviana; Reza Pratama; Abdul Mulki Irpani (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2026)
Vegetables are an important source of nutrition for humans. Katuk (Sauropus androgynus) and pegagan (Centella asiatica) are vegetables rich in nutrients and fibre, which are beneficial for the body. In addition to their many health benefits, these vegetables contain compounds that can be harmful to the body, such as nitrite (NO₂⁻). The harmful effect caused by nitrite is methemoglobinemia. This study aims to analyze the nitrite levels contained in katuk (Sauropus androgynus) and pegagan vegetables using a visible spectrophotometric method using the Griess reagent based on the diazotization reaction principle. Before the analysis of nitrite levels, method validation was carried out, including linearity, accuracy, and precision tests. From the results of the linearity test, the linear regression line equation was obtained, namely, y = 0.0551x + 0.153, r = 0.9977, BD = 0.5647 μ,g / mL, BK = 1.8824 μg / mL. The results of the similarity test obtained the coefficient of variation of the first day, 0.88%, the second 1.12%, and the third day, 1.26%. While the percentage of nitrate recovery at concentrations of 3, 6, and 9 μg / ml with the standard addition method was obtained, respectively, 116, 88, and 90%. The nitrite content in katuk yielded an average of 0,1684 mg/g, and in pegagan was 0,4218 mg/g.